Just one year - Forman, Gayle (New York : Penguin Random House Company, 2013)
"After spending an amazing day and night with a nameless girl in Paris, Willem embarks on his own transformative journey to find her once again"--
Sequel to: Just one day.
Keywords: Voyages and travels -- Fiction; Self-actualization (Psychology) -- Fiction; Love -- Fiction